"The Limits of Representative Democracy in Algeria". - OMAR. BOUDJELAL (ajps publications, 2015)
There are many studies in the field of political science which have touched on the subject of the limits of representative democracy but most of these studies have not exceeded the abstract aspect of political representation as an idea. Thus, lies the importance of this study in its scientific aspect of being a new addition to the researches that relate to the Democracy in Algeria. In the practical sense, the study aims to interrogate the Algerian reality to highlight the shortcomings that limit the optimal application of representative democracy. This scientific methodology has been employed in this study "Functional Constructivism approach" to investigate the efficacy of the different structures that react with the process of political representation. The study concluded that the political, legal and cultural structures in the frame of overall social system suffer from many crises in terms of construction and function that lead to failure in the optimal application of representative democracy in Algeria.